(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Oscillating Water Column (OWC) based wave energy conversion is one of the promising ocean energy utilisation technologies. In OWC wave energy conversion, the vertical motion of waves causes the water column in the air chamber to oscillate, generating a reciprocating motion of the air in the air chamber. This reciprocating motion rotates an air turbine and generates electricity. The characteristic feature of oscillating water column wave energy conversion is that the air turbine used in this method has a unique geometry so that the rotor always rotates in the same direction in the bi-directional airflow. One of such turbines is a counter-rotating impulse turbine for bi-directional airflow. The turbine consists of two rows of impulse rotors and their front and rear guide vanes, with both rotors counter-rotating each other. The upstream and downstream rotor rows are interchanged when the flow direction changes. The advantage of this turbine is that the two impulse rotor rows are counter-rotated, so that the energy of the airflow flowing out of the upstream rotor row can be recovered by the downstream rotor row. The authors have investigated the hydrodynamic characteristics of this turbine by using CFD analysis in previous studies, showing that they obtain higher efficiency than impulse turbine with single-stage rotors in the high flow coefficient range. However, the drawback of this turbine is that it is not very efficient despite its complex structure and high manufacturing costs. Previous experimental studies by the authors have shown that the performance of a single-stage impulse turbine for bi-directional flow can be improved by attaching end plates to the tips of the rotor blades. In this study, it is clarified that the performance of an impulse turbine with an end plate for wave energy conversion in steady flow by CFD analysis. In addition, the authors predict the performance of this turbine in unsteady flow that occurs in the real sea by quasi-steady analysis. Based on these analysis results, it evaluated the usefulness of this turbine and proposed a suitable end plate shape for improving the performance of this turbine.